MANAJEMEN STRATEGI PENINGKATAN PRESTASI AKADEMIK DAN NON-AKADEMIK DI SD MUHAMMADIYAH 15 SURABAYA - Nurkholis; Ayu Meilina Zahra; Indah Noviyanti; Shifa Istianah Azzahra; Silvia Dwi Putri; Tusinah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the management strategies to improve academic and non-academic achievements at SD Muhammadiyah 15 Surabaya. This research uses a field research method with a qualitative approach. Data were collected through observation, interviews, and documentation. The results showed that the school implements various strategies to improve student achievement, including developing soft skills, providing extracurricular activities, increasing creativity and innovation, and entrepreneurship training. In addition, the school also utilizes technology in learning, provides guidance and counseling, establishes partnerships with external parties, conducts regular evaluations, and improves teacher competence. Parental involvement is also a key factor in the success of these strategies. Keywords: Management Strategy, Academic Achievement, Non-Academic Achievement